2013
DOI: 10.1371/journal.pone.0057765
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Stimulus Sham TMS Facilitates Target Detection

Abstract: Transcranial magnetic stimulation (TMS) allows non-invasive manipulation of brain activity during active task performance. Because every TMS pulse is accompanied by non-neural effects such as a clicking sound and somato-sensation on the head, control conditions are required to ensure that changes in task behavior are indeed due to the induced neural effects. However, the non-neural effects of TMS in the context of a given task performance are largely unknown and, consequently, it is unclear what constitutes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…rSFG, rMFG, rAI, and pre-SMA were identified as target sites based on individual fMRI data (details presented below). Sham TMS was delivered on a target site located in the middle of the four empirical target sites to keep nonneural TMS effects constant (Duecker & Sack, 2013). Therefore, Talairach coordinates of the four sites were averaged and transferred back to native space to define a sham TMS target site.…”
Section: Experimental Designmentioning
confidence: 99%
“…rSFG, rMFG, rAI, and pre-SMA were identified as target sites based on individual fMRI data (details presented below). Sham TMS was delivered on a target site located in the middle of the four empirical target sites to keep nonneural TMS effects constant (Duecker & Sack, 2013). Therefore, Talairach coordinates of the four sites were averaged and transferred back to native space to define a sham TMS target site.…”
Section: Experimental Designmentioning
confidence: 99%
“…Recently, we have challenged this assumption on empirical grounds [9]. We investigated the non-neural effects of pre-stimulus TMS on target detection and revealed that the clicking sound of a sham TMS coil systematically influences task performance.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps, because of this alerting effect, accuracy performance was also slightly, although reliably, higher for TMS (86.1%) than no-TMS (85.2%) trials (t(39) = 2.19, p = .035, two tailed). This artifact renders the no-TMS trials unsuitable as a control condition (Duecker & Sack, 2013), and all further analyses focused on comparing performance between TMS conditions.…”
Section: General Tms Methodsmentioning
confidence: 99%